Analisis Yuridis Kewenangan Kepala Desa dalam Pengangkatan dan Pemberhentian Perangkat Desa Berdasarkan UU No. 6 Tahun 2014 dalam Hak dan Kewajiban di Desa Pebenaan - Bustani Bustani; KMS. Novyar Satriawan Fikri; Herdiansyah Herdiansyah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the authority of the Village Head in appointing and dismissing village officials under Law No. 6 of 2014 on Villages. It reviews theories of authority, village autonomy, governance, and the principles of good governance, while analyzing the consistency of local regulations with higher-level legislation. Using a literature review of legal documents and scholarly works, the study finds that the Village Head has attributed authority directly granted by law to recruit, appoint, and dismiss village officials. Article 50 of Law No. 6 of 2014, Article 66 of Government Regulation No. 43 of 2014, and Article 4 of Minister of Home Affairs Regulation No. 83 of 2015 confirm this authority. However, Local Regulation No. 1 of 2017 is inconsistent with these higher regulations because it grants the regency government a role in village official recruitment. In addition, the Village Head must obtain a recommendation from the Sub-district Head before appointing or dismissing officials, demonstrating that this authority remains legally limited by government and ministerial regulations.